2005
DOI: 10.1086/429391
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Antiviral 2′,5′-Oligoadenylate Synthetase (2′5′AS) Enzyme Activity Is Controlled by a Single-Nucleotide Polymorphism at a Splice-Acceptor Site in the OAS1 Gene

Abstract: It is likely that human genetic differences mediate susceptibility to viral infection and virus-triggered disorders. OAS genes encoding the antiviral enzyme 2',5'-oligoadenylate synthetase (2'5'AS) are critical components of the innate immune response to viruses. This enzyme uses adenosine triphosphate in 2'-specific nucleotidyl transfer reactions to synthesize 2',5'-oligoadenylates, which activate latent ribonuclease, resulting in degradation of viral RNA and inhibition of virus replication. We showed elsewhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
174
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(182 citation statements)
references
References 25 publications
(24 reference statements)
6
174
0
Order By: Relevance
“…The most significant probe set can hybridize only to the extended transcript variant and can thus differentiate between them; as shown in Figure 2A, not a single CEPH individual overlaps in expression level of this probe set between genotypes (P < 10 À89 ). OAS1 is an enzyme involved in innate antiviral response with splice variants that are known to affect susceptibility to viral infection (Bonnevie-Nielsen et al 2005) and multiple sclerosis (Fedetz et al 2006). The same splice site SNP known to associate with disease susceptibility was recently shown also to associate with splicing of OAS1 in CEPH cell lines (Kwan et al 2007), a finding that is confirmed by our analysis (Supplemental Fig.…”
Section: Polymorphisms Influencing Ptvsupporting
confidence: 86%
See 2 more Smart Citations
“…The most significant probe set can hybridize only to the extended transcript variant and can thus differentiate between them; as shown in Figure 2A, not a single CEPH individual overlaps in expression level of this probe set between genotypes (P < 10 À89 ). OAS1 is an enzyme involved in innate antiviral response with splice variants that are known to affect susceptibility to viral infection (Bonnevie-Nielsen et al 2005) and multiple sclerosis (Fedetz et al 2006). The same splice site SNP known to associate with disease susceptibility was recently shown also to associate with splicing of OAS1 in CEPH cell lines (Kwan et al 2007), a finding that is confirmed by our analysis (Supplemental Fig.…”
Section: Polymorphisms Influencing Ptvsupporting
confidence: 86%
“…(Graham et al 2007;Kozyrev et al 2007). b OAS1 splice variants have also been associated with multiple sclerosis (Fedetz et al 2006) and viral infectivity (Bonnevie-Nielsen et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene encoding 2Ј-5Ј-oligoadenylate synthetase-like protein 2 (Oasl2) warrants special attention. Oasl2 belongs to the IFN-induced OAS family of genes, with critical functions in innate immune responses to viruses (54,55). OAS proteins produce 2Ј-5Ј-oligoadenylates, required to activate latent ribonucleases, leading to viral RNA degradation and inhibition of viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…By alternative splicing, these genes encode 10 different isoforms, including five OAS1 isoforms (p42, p44, p46, p48, and p52), two OAS2 isoforms (p69 and p71), a single OAS3 (p100), and two OASL isoforms (p30 and p59) (13)(14)(15)(16)(17). Human OAS1, OAS2, and OAS3 are composed of one, two, and three OAS domains and form a tetramer, a dimer, and a monomer, respectively (18), whereas human OASL lacks OAS activity (15,16,19).…”
Section: Engue Virus (Den)mentioning
confidence: 99%